So sánh:
\(A=2009\cdot2011\) và \(B=2010^2\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có :
�=20092010−220092011−2<1B=20092011−220092010−2<1
⇔�<20092010−2+201120092011−2+2011=20092010+200920092011+2009=2009(20092009+1)2009(20092010+1)=20092009+120092010+1=�⇔B<20092011−2+201120092010−2+2011=20092011+200920092010+2009=2009(20092010+1)2009(20092009+1)=20092010+120092009+1=A
⇔�>�⇔A>B
Ta có :
\(B=\dfrac{2009^{2010}-2}{2009^{2011}-2}< 1\)
\(\Leftrightarrow B< \dfrac{2009^{2010}-2+2011}{2009^{2011}-2+2011}=\dfrac{2009^{2010}+2009}{2009^{2011}+2009}=\dfrac{2009\left(2009^{2009}+1\right)}{2009\left(2009^{2010}+1\right)}=\dfrac{2009^{2009}+1}{2009^{2010}+1}=A\)
\(\Leftrightarrow A>B\)
Ta có :
A=2009*2011=2009*(2010+1)=2009*2010+2009*1 = 2009*2010+2009
B=2010^2=2010*2010=2010*(2009+1)=2010*2009+ 2010*1=2010*2009+2010
Vì : 2009*2010+2009<2010*2009+2010 nên A<B